Towards the Development of Carbon Dioxide Emission Landscape in Singapore - Yong, Brandon Yung Sin (2015)
Carbon dioxide emission is an important parameter for indication of environmental impact of an industrial process. For a process that has known product capacity or revenue information, an Economic Input-Output Life Cycle Assessment (EIO-LCA) model can be applied to estimate the carbon dioxide emission. Due to the difficulty in obtaining such information for many industries, a simple linear correlation was developed using data obtained from applying EIO-LCA model on certain known processes in conjunction with the land area information obtained by ArcGIS, a geographic information software program. Jurong Island, an industrial park housing more than 100 companies in Singapore is chosen as the case study site. Carbon dioxide emission from different industrial sectors in Jurong Island were also compared.